Left ventricular functions and mass of the adolescents and young adults with thalassemia major: An echocardiography study - Muhammad Ali; Sukman Tulus Putra; Djajadiman Gatot; Sudigdo Sastroasmoro (Indonesian Pediatric Society Publishing House, 2016)
Background Thalassemia major (TM) is a transfusion-depen- dent disease. Multiple transfusions cause an accumulation of iron in the body. On the heart, iron can induce cardiomyopathy, the leading cause of death in TM. Objective To evaluate left ventricular functions and mass among adolescents and young adults with TM. Methods A cross-sectional study was conducted on 58 patients with TM in Cipto Mangunkusumo Hospital, Jakarta. Hematological data was collected from medical record. Left ventricular systolic func- tions (EF, FS), diastolic functions (A, E, E/A ratio, IVRT), and mass (LVDDi, LVDSi, LVMi) were detected using an echocardiography Sonos 4500. T test, linier regression, and multiple regression analy- sis were performed. Results Out of 32 TM patients, 30 were enrolled to study. Left ventricular systolic and diastolic functions of TM patients were lower than those of the control and statistically significant [EF 66.1% (SD 4.9) and 71.6% (SD 5.6); P<0.0001, FS 36.0% (SD 3.7) and 39.8% (SD 5.5); P=0.003, E/A 2.14 (SD 0.4) and 1.83 (SD 0.3); P=0.002, respectively]. Left ventricular mass of TM patients was greater than that of control, and also statistically significant [LVMi 111.1 g/m 2 (SD 30.8) and 75.4 g/m 2 (SD 14.5); P<0.0001, respectively]. Linier and multiple regression analysis showed significant and powerful correlation between left ventricular diastolic functions (E/A ratio) and serum ferritin concentration (r=0.71; P<0.0001). Conclusion Left ventricular functions and mass of adolescents and young adults with TM show abnormalities. The higher the con- centration of ferritin serum is, the more likely for TM patient to suf- fer from diastolic abnormality